Impacts of Fertilization Regimes on Yield and Grain Quality in Diverse Rice Genotypes Under Cold Temperate Conditions - Guo-Hua Ding; Bao-Jia Han; Kai Liu; Jin-Song Zhou; Liang-Zi Cao; Lei Lei; Liang-Ming Bai; Guang Yang; Yu Luo; Man-Li Wang; Wen-Xiu Hou; Yan-Song Ma; et al. (Agriculture)
The purpose of this research is to clarify the genetic groups associated with high-quality germplasms with different genotypes and investigate the responses of their yield and quality traits to varied fertilization regimes, thereby providing references for premium breeding and cultivation practices. A total of 29 samples, including 15 newly developed lines and 14 elite cultivars, were analyzed as to their genetic structure. A split-plot field experiment was conducted to evaluate the responses of yield, quality, and agronomic traits to different fertilization treatments. The 29 samples were classified into three genetic groups. Line 1, developed by our team, formed a unique group, while Lines 3 and 8 constituted another distinct group. In the 2022 trial, the protein content ranged from 6.8% to 9.0%, amylose content from 17.9% to 20.1%, and taste value from 73.8 to 85.7. The top five samples in yield were Line 4, Line 2, Line 5, Line 6, and Line 1, with significant differences among them (p < 0.05) and markedly higher yields compared to other samples. For taste value, Longdao 17029, Line 2, Line 4, Line 5, and Line 6 ranked highest, with Longdao 17029 exhibiting significantly superior taste scores (p < 0.05). Fertilizer treatments ranked by yield were as follows: Treatment 1 (N120P100K100) > Treatment 4 (Longfutianxia slow-release fertilizer) > Treatment 2 (N96P100K100 + bio-organic fertilizer) > Treatment 3 (N0P0K0), with significant differences (p < 0.05). Treatment 2 achieved a significantly higher taste value than the others (p < 0.05). In the 2023 trial, Longdao 17029 demonstrated higher leaf color index and net photosynthetic rate during the grain-filling stage, compared to Longdao 18 and Longdao 21. Lines 1, 3, and 8 are valuable for broadening the genetic diversity of rice in cold regions. Line 4 and Longdao 17029 show potential as novel germplasms for improving yield and taste quality. Moderate nitrogen reduction, combined with bio-organic fertilizer application, enhances rice taste value.